Nurses' salaries in Indonesia - Joko Gunawan (Belitung Raya Foundation, 2022)
This article aims to describe salary of nurses in Indonesia based on employment status, place of work, and geographical context. The information presented in this paper can be used as basic data or a reference in choosing a job or a career in nursing.